2009
DOI: 10.1007/s11745-009-3310-x
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Bilayer Phospholipid Composition and Curvature on Ligand Transfer by the α‐Tocopherol Transfer Protein

Abstract: We report here our preliminary investigations on the mechanism of alpha-TTP-mediated ligand transfer as assessed using fluorescence resonance energy transfer (FRET) assays. These assays monitor the movement of the model alpha-tocopherol fluorescent derivative ((R)-2,5,7,8-tetramethyl-chroman-2-[9-(7-nitro-benzo[1,2,5]oxadiazol-4-yl amino)-nonyl]-chroman-6-ol; NBD-Toc) from protein to acceptor vesicles containing the fluorescence quencher TRITC-PE. We have found that alpha-TTP utilizes a collisional mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 88 publications
4
24
0
Order By: Relevance
“…The α-TTP/ α-TOH complex moves to the plasma membrane where it is targeted by phosphatidylinositol bisphosphates (PIP2), which are essential interaction partners of α-TTP [76] . In this case, α-TTP has been shown to transfer α-TOH between membranes through direct proteinmembrane interactions [111][112][113] . In brief, experiments with liposomes have revealed that α-TTP acts as an α-TOH/ PIP2 exchanger [76] .…”
Section: Intracellular Binding Proteins α -Tocopherol Transfer Proteinmentioning
confidence: 99%
“…The α-TTP/ α-TOH complex moves to the plasma membrane where it is targeted by phosphatidylinositol bisphosphates (PIP2), which are essential interaction partners of α-TTP [76] . In this case, α-TTP has been shown to transfer α-TOH between membranes through direct proteinmembrane interactions [111][112][113] . In brief, experiments with liposomes have revealed that α-TTP acts as an α-TOH/ PIP2 exchanger [76] .…”
Section: Intracellular Binding Proteins α -Tocopherol Transfer Proteinmentioning
confidence: 99%
“…Hypothetically, this ␣ -tocopherol transfer function is necessary for the observed mechanism that enriches the plasma with ␣ -tocopherol, not with the other non-␣ -tocopherol ( 43,60,61 ). Notably, the liver ( 62 ), not the intestine, expresses ␣ -TTP; thus, liver, not the intestine, specifi cally discriminates between forms of vitamin E. The means by which ␣ -TTP facilitates ␣ -tocopherol secretion into plasma is unknown, but it is under investigation (63)(64)(65)(66)(67)(68)(69)(70). The current consensus is that syndromes ( 23 ), if the vitamin E is given as a stable micellar form ( 24 ).…”
Section: Hepatic Secretion Of ␣ -Tocopherol Into Plasmamentioning
confidence: 99%
“…The hope is that a-tocohexaenol will be able to be used in a similar fashion as cis-parinaric acid, but be able to report more specifically on the location of tocopherol in a membrane. Other fluorescent analogues of tocopherol including C9-NBD-a-tocopherol [87] and C8-BODIPY-a-tocopherol (West, R., submitted) have been useful in determining the cellular location and transfer of tocopherol [88][89][90][91][92], but do not change fluorescence on oxidation.…”
Section: Do We Know Where Tocopherol Does Its Most Important Job?mentioning
confidence: 99%